Nuclear energy consumption, low-carbon transition and factor productivity in South Korea - Muhammad Yousaf Raza; Yingchao Chen (Nuclear Engineering and Technology)
South Korea has one of the youngest reactor fleets of nuclear in the world. Under the “Green Deal,” South Korea's nuclear energy is projected to rise abundantly. The study objective is to examine energy-economic-related factors, including fuel energy structure, non-renewable structure, gross domestic product (GDP) per capita, energy intensity, and population using the decomposition and decupling approaches from 1979 to 2023. The results show that (i) under the economic planning period, energy intensity in the nuclear energy efficiency impacts both the economy and production process; however, GDP per capita and population are the major factors in nuclear energy growth, adding 0.22 % and 2.35 % during the estimated period. (ii) Four decouplings were found under the five-year economic planning, in which weak and expansive decoupling was seen in the majority; however, the current decade provides strong decoupling with efficient nuclear energy productivity, presenting that nuclear energy is the leading source in the economic development. (iii) Annual decoupling indexes of individual factors present the expansive negative, weak and strong decoupling in which decoupling relationship between expansive and weak was gradually dominated by strong decoupling and estimated between −0.11 % and 0.54 %, respectively. Finally, based on novel mechanisms, including environmental factors, industrial contribution and transition towards nuclear energy that favor energy and economic sustainability can be implemented in the future.